Free-breathing post-contrast three-dimensional T1 mapping: volumetric assessment of myocardial T1 values - Weingärtner, Sebastian (Magnetic resonance in medicine, 2014)
Purpose: To develop a three-dimensional (3D) free-breathing myocardial T1 mapping sequence for assessment of left ventricle diffuse fibrosis after contrast administration. Methods: In the proposed sequence, multiple 3D inversion recovery images are acquired in an interleaved manner. A mixed prospective/retrospective navigator scheme is used to obtain the 3D Cartesian k-space data with fully sampled center and randomly undersampled outer k-space. The resulting undersampled 3D k-space data are then reconstructed using compressed sensing. Subsequently, T1 maps are generated by voxel-wise curve fitting of the individual interleaved images. In a phantom study, the accuracy of the 3D sequence was evaluated against two-dimensional (2D) modified Look-Locker inversion recovery (MOLLI) and spin-echo sequences. In vivo T1 times of the proposed method were compared with 2D multislice MOLLI T1 mapping. Subsequently, the feasibility of high-resolution 3D T1 mapping with spatial resolution of 1.7 × 1.7 × 4 mm3 was demonstrated. Results: The proposed method shows good agreement with 2D MOLLI and the spin-echo reference in phantom. No significant difference was found in the in vivo T1 times estimated using the proposed sequence and the 2D MOLLI technique (myocardium, 330 ± 66ms versus 319 ± 93 ms; blood pools, 211 ± 68 ms versus 210 ± 98 ms). However, improved homogeneity, as measured using standard deviation of the T1 signal, was observed in the 3D T1 maps. Conclusion: The proposed sequence enables high-resolution 3D T1 mapping after contrast injection during free-breathing with volumetric left ventricle coverage.
Gesehen am 30.08.2017
Im Titel ist "1" tiefgestellt